Penerapan Implementasi ISAK 35 Pada Masjid (Studi Kasus Masjid di Kecamatan Medan Kota) - Fatika, Siti; Nasution, Yenni Samri Juliati; Lubis, Arnida Wahyuni (Universitas Labuhanbatu, 2023)
This research aims to find out mosque administrators in Medan Kota Subdistrict have prepared financial reports based on ISAK 35, to find out the implementation of mosque financial reports in Medan Kota Subdistrict based on ISAK 35 and to determine the suitability of mosque financial reports against ISAK 35. The type of research used is qualitative. The research subjects in this study were the mosque treasurer and the chairman of the Mosque Welfare Board (BKM) totaling 3 respondents. The data obtained are primary and secondary data. Data collection techniques using interviews, observation and documentation. The results showed that first, the preparation of financial statements carried out by each treasurer of the Silaturrahim Mosque, Islamiyah Mosque and Al-Muhajirin Mosque was not in accordance with ISAK No. 35. Second, the implementation of mosque financial reports in Medan Kota Sub-district based on ISAK 35 contained in the three mosques is not in accordance with ISAK 35, namely in the form of preparing a statement of financial position, statement of comprehensive income, statement of changes in net assets, cash flow statement, and notes to financial statements. Third, the suitability of the financial statements of the Islamiyah and Al-Muhajirin mosques is not appropriate, which is only limited to recording mosque income and expenses. Meanwhile, with the Silaturrahim Mosque, although it is not in accordance with applicable accounting standards, this mosque describes the financial records applied in each of the financial statements that I have prepared.